Relief and care in the shade: A concept extracted from practices of neonatal nurses during pain management - Zahra Hadian Shirazi; Mitra Soltanian; Raheleh Sabet Sarvestani (Tehran University of Medical Sciences, 2020)
Background & Aim: Nowadays, despite the improvements in the knowledge and attitude of healthcare professionals, there are still obstacles against pain management in Neonatal Intensive Care Units (NICUs). Hence, it is necessary to know about the problems of pain management in NICUs. This research aimed to explore the pain management experiences of NICU nurses and neonatologists. Methods & Materials: This content analysis study was conducted on six experienced NICU nurses and two neonatologists in one hospital affiliated to Shiraz University of Medical Sciences who were selected through purposive sampling which continued until saturation. The data were collected through semi-structured interviews and field notes. The data were simultaneously analyzed using inductive content analysis. Results: Analysis of the data generated one theme and three categories and seven subcategories. The theme was "pain relief in the shade". The categories were "responsibility versus ignorance", "family caregiver as a barrier or facilitator", and "newborn, sacrificed due to imbalanced context". This study showed that professional caregivers managed pain on the margin of other cares. The effects of family care were identified as a paradox, helping, or disturbing. The participants also emphasized the impact of environmental disruptions on pain management. Conclusion: The experiences of pain management in NICUs were identified at three levels of professional caregivers, family caregivers, and organizational atmosphere. Exploring this experience could help improve pain management and reduce its side effects in susceptible neonates. Hence, healthcare workers are recommended to ensure effective pain management in NICUs by ongoing monitoring and audit.